Reforming the Brazilian Supreme Federal Court: a Comparative Approach - Maria Angela Jardim de Santa Cruz Oliveira (Washington University Global Studies Law Review, 2006)
This Article defends giving the SFC power to issue provisional measures to stay the proceedings of identical cases in lower courts when the constitutional controversy has already been presented before the SFC.
Keywords: Judicial reform; Judicial review; Comparative law; Constitutional law; Brazil. Supremo Tribunal de Justica